THREAT PERCEPTION AND TURKEY`S OFFENSIVE FOREIGN POLICY BEHAVIOR IN THE SYRIAN CRISIS - Mahdieh Heidari, Ellias Aghili Dehnavi, Amir Parvaresh, Mohammad Ghanbari Barzyan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This essay explores the perspective of Turkey's aggressive behavior on the Syrian crisis in an exploratory way with Stanford's school perspective. So the main question is, what is the reason behind Turkey's changing behavior or foreign policy in the Syrian crisis and making it more aggressive? The provisional answer is that key Turkish decision-makers understand the potential for instability and extremism to overtake Turkey's inland borders, the likelihood of Syrian Kurdish autonomy and the threat to security of Turkey's internal borders, as well as the country's geopolitical ambitions, foreign policy. They have been more aggressive in the face of the Syrian crisis since 2016. The findings of the Stanford School study suggest that Turkish decision-makers have intensified Turkey's maximal violence against the Syrian crisis by intensifying its understanding of the threats to Turkey's national interests. In other words, there was a positive correlation between the amount of violence received in Turkey and the amount of violence used in the Syrian crisis. The method of data collection in this research is based on the library method which consists of simultaneous use of internal and external scientific articles.